2013
DOI: 10.1590/s0102-79722013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Stressful events in autobiographical memory processing: Brazilian version of the centrality of event scale

Abstract: A stressful or traumatic event may become a central reference point in the organization of long-term memory, influencing the meaning of other experiences. The Centrality of Event Scale (CES) is an instrument in which participants recall the most traumatic event of their life and endorse 20 items. The CES was translated, adapted and validated for the Brazilian context in a sample of 195 undergraduates (75.8% women). The version obtained good internal consistency and significant correlation with a screening meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 20 publications
2
32
1
7
Order By: Relevance
“…It did not achieve acceptable fit indicators (see Table 2; AIC = 29712.818). Gauer et al (2013) also suggested a short version of the CES, which proved to be an acceptable fit to the combined sample used in the current work (see Table 2; AIC = 29415.849). Lastly, a three-factor measurement model allocating each of the seven items selected by Berntsen and Rubin (2006) to their intended content was also tested via CFA.…”
Section: Centrality Of Event For Adolescents -Short Versionmentioning
confidence: 68%
See 2 more Smart Citations
“…It did not achieve acceptable fit indicators (see Table 2; AIC = 29712.818). Gauer et al (2013) also suggested a short version of the CES, which proved to be an acceptable fit to the combined sample used in the current work (see Table 2; AIC = 29415.849). Lastly, a three-factor measurement model allocating each of the seven items selected by Berntsen and Rubin (2006) to their intended content was also tested via CFA.…”
Section: Centrality Of Event For Adolescents -Short Versionmentioning
confidence: 68%
“…It will be up to the researcher or clinician to choose at each time which version of the instrument best suits his/her goals. Note: CES-A = Centrality of Event for Adolescents; CFA = confirmatory factor analysis; (0) refers to the measurement models suggested by Bernstein and Rubin (2006); (1) refers to the measurement models suggested by Gauer et al, (2013); (2) Note. All loading values were significant at p < .001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies with non‐English speaking samples with different cultural backgrounds have shown different factor structures. For example, the Brazilian Portuguese version of the 20‐item CES (Gauer et al, ) evidenced three factors for both versions, and the Portugal Portuguese Adolescent version showed a three‐factor structure for the 20‐item version but a one‐factor structure for the 7‐item version (Vagos et al, ). In addition, the study conducted by Robinaugh and McNally () also found a three‐factor structure with the original 20‐item version (Robinaugh & McNally, ).…”
Section: Discussionmentioning
confidence: 99%
“…While the preliminary research with the CES is promising, there remains some controversy about its factor structure. For example, in an exploratory principal components analysis, the Brazilian Portuguese version of the 20‐item evidenced three components with eigenvalues greater than one in a sample of young adults (Gauer, de Souza, da Silveira, & Sediyama, ). Robinaugh and McNally () also found that the 20‐item version of the CES best represented three factors (Robinaugh & McNally, ).…”
Section: Introductionmentioning
confidence: 99%